PERSEPSI MASYARAKAT NELAYAN TERKAIT REVITALISASI PELABUHAN PERIKANAN POPOH KABUPATEN TULUNGAGUNG - Irma Ul Chusna; Sholih Muadi; Edi Susilo (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2019)
The existence of the marine and fisheries sector and the management of coastal areas and small islands is one of the national development agendas. But in fact, the development of the maritime and fisheries sector has not yet been used optimally, so as to make the maritime and fisheries sector as the main stream of national development an integrated and ecosystem-based development policy is needed. is to build fisheries infrastructure in the form of fishing ports for fishing communities in the coastal areas of East Java, one of which is the Popoh fishing port in Tulungagung. The construction of the port was carried out by the Regional Government of East Java Province through the Department of Marine and Fisheries based on the East Java Provincial Budget. It is hoped that with the existence of the Popoh Fisheries Port, the coastal communities of Popoh and its surrounding areas, most of whose residents work as fishermen, can receive the benefits of the port. With the activity of developing the Popoh Fisheries Port automatically these conditions trigger a perception from the surrounding fishing community. The results showed that there were positive and negative perceptions related to the revitalization of the popoh fishing port in Tulungagung. The existence of a positive or good perception in the aspects of cognition, affection, and konasi can lead to good or positive social action on the Popoh fishing community towards the revitalization of the Popoh Fishing Port.